Wall enhancement characteristics of vertebrobasilar nonsaccular aneurysms and their relationship to symptoms. Issue 129 (August 2020) - Cao, Lizhen; Zhu, Chengcheng; Eisenmenger, Laura; Du, Xiangying; Liu, Jiabin; Yang, Qi; Lu, Jie; Li, Kuncheng; Saloner, David
Highlights: Wall enhancement correlates with symptomatic vertebrobasilar nonsaccular aneurysms (VBNAs). Wall enhancement characteristics of VBNAs can be quantitatively analyzed. Wall enhancement ratio is an important indicator of symptomatic VBNAs. Abstract: Purpose: This study aims to explore wall enhancement characteristics of vertebrobasilar nonsaccular aneurysms (VBNAs) and their relationship to clinical symptoms. Methods: We retrospectively analyzed VBNAs in the high resolution MR vessel wall imaging (HR-VWI) databases at two institutions. The aneurysmal basic characteristics and wall enhancement characteristics, were evaluated by two radiologists. The aneurysmal basic characteristics were location, type, the maximal outer diameter (Dmax ), T1 hyperintensity, and mural thrombus. The wall enhancement characteristics included the presence or absence of enhancement, enhancement distribution (concentric or eccentric), enhancement grades (<50% & 50%), enhancement index ((SIwall-post /SIbrain-post - SIwall-pre /SIbrain-pre )/ (SIwall-pre /SIbrain-pre )), enhancement ratio (SIwall-post /SIpituitary-post ), and enhancement extent (focal BA, whole BA, and VBA). The VBNAs' related symptoms of all cases were identified. The associations of aneurysmal basic characteristics and wall enhancement characteristics with symptoms were analyzed. Results: 34 VBNAs cases were included in the final analysis. Of the 34 cases, 18 cases (52.9%) presented VBNAs' related symptoms. Aneurysmal characteristics associated with symptoms were transitional type (P = 0.015), Dmax (P < 0.001), T1 hyperintensity (P = 0.003), mural thrombus (P < 0.001), the presence of enhancement (P = 0.003), enhancement index (P = 0.031), and enhancement ratio (P < 0.001). Aneurysmal characteristics that were independently associated with symptoms were Dmax (OR = 1.406, P = 0.013) and enhancement ratio (OR = 9.83, P = 0.037). In ROC curve analysis, AUC of the joint variable (Dmax and enhancement ratio) was 0.92, and the sensitivity and specificity were 94.4% and 87.5%, respectively. Conclusion: Wall enhancement correlates with symptomatic VBNAs. Dmax and enhancement ratio of aneurysmal wall are important indicators to instable status of symptomatic VBNAs.